Genome Compositional Organization in Gars Shows More Similarities to Mammals than to Other Ray-Finned Fish - Symonová, Radka; Majtánová, Zuzana; Arias-Rodriguez, Lenin; Mořkovský, Libor; Kořínková, Tereza; Cavin, Lionel; Pokorná, Martina Johnson; Doležálková, Marie; Flajšhans, Martin; Normandeau, Eric; Ráb, Petr; Meyer, Axel; et al. (Journal of experimental zoology. Part B, Molecular and developmental evolution, 2017)
Genomic GC content can vary locally, and GC-rich regions are usually associated with increased DNA thermostability in thermophilic prokaryotes and warm-blooded eukaryotes. Among vertebrates, fish and amphibians appeared to possess a distinctly less heterogeneous AT/GC organization in their genomes, whereas cytogenetically detectable GC heterogeneity has so far only been documented in mammals and birds. The subject of our study is the gar, an ancient "living fossil" of a basal ray-finned fish lineage, known from the Cretaceous period. We carried out cytogenomic analysis in two gar genera (Atractosteus and Lepisosteus) uncovering a GC chromosomal pattern uncharacteristic for fish. Bioinformatic analysis of the spotted gar (Lepisosteus oculatus) confirmed a GC compartmentalization on GC profiles of linkage groups. This indicates a rather mammalian mode of compositional organization on gar chromosomes. Gars are thus the only analyzed extant ray-finned fishes with a GC compartmentalized genome. Since gars are cold-blooded anamniotes, our results contradict the generally accepted hypothesis that the phylogenomic onset of GC compartmentalization occurred near the origin of amniotes. Ecophysiological findings of other authors indicate a metabolic similarity of gars with mammals. We hypothesize that gars might have undergone convergent evolution with the tetrapod lineages leading to mammals on both metabolic and genomic levels. Their metabolic adaptations might have left footprints in their compositional genome evolution, as proposed by the metabolic rate hypothesis. The genome organization described here in gars sheds new light on the compositional genome evolution in vertebrates generally and contributes to better understanding of the complexities of the mechanisms involved in this process.
Keywords: časové faktory; genom; Genomics; ryby; savci; genomika; Computational Biology; Karyotype; Time Factors; karyotyp; Phylogeny; Genome; výpočetní biologie; Animals; Fishes; zvířata; Mammals; fylogeneze